Digital Inclusion for Seniors: Assessing Chat Application Skills in Senior Digital Academy Programs - Rita Gani; Citra Rosalyn Anwar; Sari, Mutiara Dwi (Universitas Muhammadiyah Yogyakarta, 2025)
The digitalization of modern society requires older generations to adapt to internet-based communication, but age-related limitations often hinder this transition. This study explores the proficiency of elderly participants in using chat applications through the Senior Digital Academy (ADL) program by Tular Nalar Mafindo. Using a descriptive qualitative method, surveys and in-depth interviews were conducted with 61 senior participants. Findings show that while seniors understand basic chat application features and their potential negative impacts, they face challenges like digital literacy gaps, technological anxiety, and physical limitations. Many struggle with advanced features such as multimedia sharing, privacy settings, and group management. Vision impairments, reduced motor skills, and cognitive decline further complicate their use of digital tools. Despite these obstacles, participants express a strong willingness to learn and recognize the importance of staying connected through digital platforms. The study emphasizes the need for tailored digital literacy programs to address the specific needs of older adults, enabling them to navigate the digital world more effectively. Empowering seniors through digital literacy not only fosters social connectivity and independence but also mitigates risks like misinformation, hate speech, and fraud, ensuring their inclusion and safety in an increasingly online society.